Virtual Counseling for Students Enrolled in Online Educational Programs - Nikki S. Currie (Educational Considerations, 2010)
Virtual schools are increasing in popularity as a method of providing formal education for a growing number of students in the United States.
Keywords: formal; education; virtual; counseling; students; online; educational; programs; reality